PENGARUH LITERASI DIGITAL DAN TINGKAT PENDIDIKAN TERHADAP KESIAPAN KERJA MASYARAKAT DI KABUPATEN ACEH TENGGARA - Desi Aramana (SUAN PUBLISHER, 2026)
The accelerating digital transformation has fundamentally reconstructed the modern employment landscape, demanding the integration of technological proficiency and formal educational foundations. In developing regions with mountainous geographical characteristics such as Southeast Aceh Regency, workforce competitiveness challenges are exacerbated by gaps in digital utilization and disparities in educational attainment. This study aims to analyze and empirically demonstrate the effect of digital literacy and educational level on the work readiness of productive-age communities in Southeast Aceh Regency, both partially and simultaneously. Employing an explanatory correlational quantitative approach, this study surveyed 135 productive-age respondents (15–64 years) selected through purposive sampling. Primary data were gathered via a structured 5-point Likert scale questionnaire tested for validity and reliability, and subsequently analyzed using multiple linear regression in IBM SPSS version 26. The empirical findings reveal that digital literacy has a positive and significant effect on work readiness (; ), and educational level similarly exerts a positive and significant effect on work readiness (; ). Simultaneously, both independent variables significantly influence work readiness (; ) with a coefficient of determination () of 0.495. This indicates that 49.5% of the variance in community work readiness is accounted for by digital literacy and education level, while the remaining 50.5% is driven by unmodeled external factors. These findings underline the urgent necessity for policy interventions focusing on productive digital competency enhancement and vocational/higher education alignment in non-metropolitan regions